ANALISIS PENGARUH TINGKAT PEREKONOMIAN KELUARGA TERHADAP PERILAKU KONSUMTIF MASYARAKAT DESA SETELUK ATAS KABUPATEN SUMBAWA BARAT - Farida Riani; Roos Nana Sucihati (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of the family's economic level on the consumptive behavior of the people at Seteluk Atas Village. The variables in this study are the family's economic level as the independent variable and the consumptive behavior of the people as the dependent variable. Data collection was obtained through the distribution of questionnaires. Data were analyzed by calculating simple linear regression, partial test and determinant coefficient (R2). The results showed that the level of the family's economy had a positive and significant effect on the acceptance of consumptive behavior in the people of Seteluk Atas Village. The ability of the family's economic level in influencing changes on the consumptive behavior of the people at Seteluk Atas Village is 51%, while the remaining 49% is influenced by other factors not examined.